Managing future oil revenues in Ghana: An assessment of alternative allocation options - Breisinger, Clemens; Diao, Xinshen; Schweickert, Rainer; Wiebelt, Manfred (Wiley, 2010)
Abstract:  Contemporary policy debates on the macroeconomics of resource booms often concentrate on the short‐run Dutch disease effects of public expenditure, ignoring the possible long‐term effects of alternative revenue‐allocation options and the supply‐side impact of royalty‐financed public investments. In a simple model applied here, the government decides the level and timing of resource‐rent spending. This model also considers productivity spillovers over time, which may exhibit a sector bias toward domestic production or exports. A dynamic computable general equilibrium (DCGE) model is used to simulate the effect of temporary oil revenue inflows to Ghana. The simulations show that beyond the short‐run Dutch disease effects, the relationship between windfall profits, growth, and households’ welfare is less straightforward than what the simple model of the ‘resource curse’ suggests. The DCGE model results suggest that designing a rule that allocates oil revenues to both productivity‐enhancing investments and an oil fund is crucial to achieving shared growth and macroeconomic stability.